DANCING COMMUNICATION DURING AN ERA OF DIGITAL TECHNOLOGIES - Zh. V. Pimenova (Научный вестник МГТУ ГА, 2016)
In the present article influence of digital technologies on art development as large-scale phenomenon of modern culture is considered. The mechanism of coverage of choreographic statements in the context of the Internet is for the first time analyzed. The value of esthetic impact of dance as form of art communication on consciousness of the viewer becomes clear. Possibilities of choreography are defined as genre of art to change the nature of thinking of the public from the point of view of esthetic preferences. Short digression to history of emergence of computers is given. The role of dancing language within Internet communications from a position of its advertizing effect is emphasized. Examples of the modern choreographic performances which are positioned in a digital format are given.